COMMUNITY EMPOWERMENT PASSIVE ROM (RANGE OF MOTION) TRAINING ON REHABILITATIVE POST-STROKE PATIENTS - Ixora, Ixora; Wulandari, Dewi; Yulidaningsih, Elok (SYNTHESIS Global Health Journal, 2025)
Background. Stroke is a non-communicable disease, and the number of cases continues to increase every year. Proper treatment after a stroke determines the patient's maximum recovery rate. Until now, the incidence of stroke continues to increase, which is due to the lack of information among post-stroke patients about stroke care at home. Most of them only get information regarding stroke nutritional diets, even though they also have to be trained physically, one of which is ROM (Range of Motion).  This Community Service activity aims to improve the knowledge and behavior of elderly cadres at the Bandung community health center. Implementation Method. Community service methods are pre-test and post-tests, with activities ranging from counseling about stroke and how to prevent stroke, outreach, ROM training for rehabilitation of post-stroke patients, assistance with ROM training, and evaluation of elderly posyandu cadres. The number of respondents targeted for this community service was 50 health cadres and the elderly in Suruhan Kidul village, Bandung Community Health Center working area, Tulungagung District. Findings. The result of community service based on observation and evaluation is an increase in the knowledge and skills of health cadres and the elderly regarding rehabilitative actions for stroke patients (ROM). Conclusion. Community service in the form of counseling and training carried out in Suruhan Kidul Village, Bandung Community Health Center working area, Bandung District, Tulungagung Regency, generally provides benefits to health cadres and the elderly. Cadres and the elderly have the knowledge and skills for stroke rehabilitation (ROM).